PENGARUH CAMPURAN SERAT BAJA PADA BETON GEOPOLIMER DITINJAU KUAT TARIK BELAH - Vahlefi M., Muhammad; Putrianti, Pratika Riris; Setiawan, Agustinus Agus (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2024)
Geopolymer concrete has decent strength, but it is still lower compared to conventional concrete. One way to improve the strength of geopolymer concrete is by adding reinforcing fibers. The fibers used should be suitable for the environmental conditions and economical. One fiber that can be used to enhance the strength of concrete is steel fiber. The addition of steel fiber to concrete can increase its density but may decrease the slump value, which can affect the workability of the concrete. In BGP 1%, the increase from 0% fiber content reaches 3.2%, and in BGP 2%, it reaches the maximum density of 2405.73 kg/m3 with the addition of fiber to geopolymer concrete. From the results, it can be observed that as the density of geopolymer concrete increases, the slump value tends to decrease.